Complex grade III astrocytoma with granular cells and PXA features in a patient with tuberous sclerosis complex (Bourneville-Pringle syndrome) – case report and review of literature - Mucha-Małecka, Anna; Małecki, Krzysztof; Kurzyński, Michał; Adamek, Dariusz; Biesaga, Beata; Urbanek, Konrad; Grela-Wojewoda, Aleksandra; Pluta, Elżbieta; Patla, Anna; Modrzejewski, Maciej; Blecharz, Paweł; Amrogowicz, Natalia (Polish Journal of Pathology, 2021)
Tuberous sclerosis complex (Bourneville-Pringle syndrome) is a rare genetic condition included in the group of diseases called phakomatoses. Most of the patients are diagnosed with abnormalities within the central nervous system and tend to develop tumors more frequently, especially gliomas. We present a case of 50-year-old patient suffering from tuberous sclerosis complex, who had been diagnosed with pleomorphic xanthoastrocytoma (PXA). The patient underwent surgery and adjuvant radiotherapy and has remained free from local recurrence for 5 years.